Cataloguing LGTBIQ+ characters in Disney children’s animation - Cárdenas Rica, María Luisa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Gender diversity is beginning to have a place in children's animated films. Disney contributes to its dissemination, its protagonists are part of visual culture and are a point of reference. The study has catalogued the LGTBIQ+ characters linked to the century-old company. With this intention, their characteristics and the leading role they play have been analysed, which will allow us to find out the closeness and possible identification of the young recipients with the non-heteronormative characters. The research reveals that their visibility is still limited, and that there is still a long way to go to ensure that no identity goes unnoticed.